2020
DOI: 10.3390/ijms21207724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silymarin Supplementation on Physical Performance, Muscle and Myocardium Histological Changes, Bodyweight, and Food Consumption in Rats Subjected to Regular Exercise Training

Abstract: (1) Background: Regular exercise induces physiological and morphological changes in the organisms, but excessive training loads may induce damage and impair recovery or muscle growth. The purpose of the study was to evaluate the impact of Silymarin (SM) consumption on endurance capacity, muscle/cardiac histological changes, bodyweight, and food intake in rats subjected to 60 min of regular exercise training (RET) five days per week. (2) Methods: Male Wistar rats were subjected to an eight-week RET treadmill pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…The elevated demand of oxygen (O 2 ), fundamentally in endurance ET, promotes the inflammatory response along with modifications of the airways, and is accompanied by changes in other organs such as muscle and myocardium. It appears that the use of silymarin exhibits a benefit on the recovery and hypertrophy of quadriceps and gastrocnemius muscle and the myocardium, together with an increase in maximal endurance capacity and the improvement of the lean muscle mass and body weight of rats subjected to regular exercise training, as our research has previously reported [5]. During exertion, there is a multi-organ-function coupling triggered by muscle power in a demand for O 2 -rich blood; thus, pulmonary function is basically implicated in O 2 and CO 2 exchange and transport.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The elevated demand of oxygen (O 2 ), fundamentally in endurance ET, promotes the inflammatory response along with modifications of the airways, and is accompanied by changes in other organs such as muscle and myocardium. It appears that the use of silymarin exhibits a benefit on the recovery and hypertrophy of quadriceps and gastrocnemius muscle and the myocardium, together with an increase in maximal endurance capacity and the improvement of the lean muscle mass and body weight of rats subjected to regular exercise training, as our research has previously reported [5]. During exertion, there is a multi-organ-function coupling triggered by muscle power in a demand for O 2 -rich blood; thus, pulmonary function is basically implicated in O 2 and CO 2 exchange and transport.…”
Section: Introductionsupporting
confidence: 78%
“…The administration of silymarin significantly optimized the race time and distance covered when compared with the other groups in the maximal effort test. In turn, it is suggested that silymarin helped to improve physical performance and induced myocardium and quadriceps/gastrocnemius muscle recovery and remodeling and improved body composition, by expanding lean muscle mass, after an 8-week exercise-training program [ 5 ]. To continue with this line of research, in the present work the hepatic changes included an increase in vascularization, specifically in the groups treated with antioxidants, and also the reduction of steatosis in all of the trained groups, with an even greater reduction observed in the group with silymarin, which was remarkably similar to that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, SM (20 mg/kg/day i.p, 4 weeks) was demonstrated to enhance the expression of SIRT1 associated with decreased expression of NF-κB, providing anti-inflammatory effects in the hippocampus of old male rats [127]. In addition, SM was indicated to improve muscle recovery and to ameliorate inflammation and damaged tissue in rats subjected to regular exercise training [128]. Finally, a reduction in lung tissue inflammation was evident in rats subjected to 8-week exercise training due to the administration of SM (100 mg [129]).…”
Section: Ageing and Exercising Modelsmentioning
confidence: 98%
“…Our research group found that silymarin, the flavonolignan extract from Milk thistle, has been demonstrated to increase physical performance and to promote muscle hypertrophy and recovery at doses of 100 mg/kg after eight weeks of regular exercise in a rodent model [114]. Aside, the pretreatment with sulforaphane (SFN) from broccoli in 13-week-age Nrf2+/+ and Nrf2−/− male mice upregulated Nrf2 signaling and downstream genes, improved the endurance capacity associated with a lower OS marker, and provided protection against muscle fatigue during exhaustive exercise.…”
Section: General View Of Antioxidants Oxidative Stress and Exercise Performancementioning
confidence: 99%